2005
DOI: 10.1093/cercor/bhj117
|View full text |Cite
|
Sign up to set email alerts
|

Time Representations Can Be Made from Nontemporal Information in the Brain: An MEG Study

Abstract: Perceiving the passage of time is an essential ability for humans and animals. Here we used magnetoencephalography and investigated how our internal clock system in the brain converts sensory experiences into their time representations. We focused on neural activities in the high-level visual areas of human subjects when they saw visual patterns and estimated the duration of their presentation. The activities in the visual areas could give us neural indices about when subjects perceived the appearance and disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 54 publications
6
50
0
Order By: Relevance
“…These recent papers complement previous work on human timing by Noguchi and Kakigi (2006), who used magnetoencephalography (MEG) to record visuallyevoked activity during a temporal discrimination task in which human observers judged whether the second of two visually presented stimuli had a "longer" or "shorter" duration than the first. They assessed both behavioral responses and the "neural interval", defined as the time between the evoked neural responses to the onset and offset of the durations.…”
Section: Linking Repetition Suppression To Subjective Timesupporting
confidence: 67%
“…These recent papers complement previous work on human timing by Noguchi and Kakigi (2006), who used magnetoencephalography (MEG) to record visuallyevoked activity during a temporal discrimination task in which human observers judged whether the second of two visually presented stimuli had a "longer" or "shorter" duration than the first. They assessed both behavioral responses and the "neural interval", defined as the time between the evoked neural responses to the onset and offset of the durations.…”
Section: Linking Repetition Suppression To Subjective Timesupporting
confidence: 67%
“…A similar lack of observed involvement of the SMA is reported in the work of Sieroka et al (2003), as they identified the posterior cingulate gyrus as the source of slow magnetic fields observed during the perception of 1.4 s intervals, and by the MEG study of Gómez et al (2004) in which no involvement of the SMA was found in a foreperiod paradigm. Offsetting the studies that did not find evidence for the involvement of the SMA, Noguchi and Kakigi (2006) showed that magnetic activity in the SMA increased during the perception of intervals shorter than 1 s. This incongruity could partly be accounted for by the different responding regimes that were employed. In the study by Noguchi and Kakigi (Noguchi, 2014, personal information) study, participants always responded with their right thumb, whereas either with the right or left thumb in the study of N'Diaye et al (2004).…”
Section: Introductionmentioning
confidence: 91%
“…Both the current study and the study by N'Diaye et al (2004) employed magnetometers. However, Noguchi and Kakigi (2006) used planar gradiometers, which might have allowed them to find slow magnetic shifts. Moreover, in the context of unraveling weak magnetic fields from the SMA and ACC it may be crucial for future studies to obtain individual brain scans that can tremendously improve the accuracy of source reconstruction.…”
Section: Amplitude Of Electromagnetic Signals and Timing Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…3A) were averaged. stimuli (offset neural response) (Kinoshita & Komatsu, 2001;Noguchi & Kakigi, 2006). Although we have interpreted the MEG waveforms at 200e500 msec as the CRAs, it is possible that those MEG components simply reflected the offset neural responses, not conscious perception of the RP.…”
Section: An Effect Of the Offset Neural Response On Meg Waveformsmentioning
confidence: 98%